Obszar wiejski jako segment rynku politycznego w III Rzeczypospolitej - Dzieciński, Paweł (Zeszyty Wiejskie, 2010)
One of important criterion of identity political market is a territorial division. In every country a very important political market segment is a country area. It include villages and little towns connected with agriculture. When came into existence the democracy in Poland, the country political market was homogeneous and very different from towns political market. In later years was in the country area the economic crisis and out of polish parties only the Polish Peasants‟ Party managed to win a majority of votes in the country area (1993). The Polish Peasants‟ Party had the attractive for country votes an electoral programme. But in later years on the political stage launched an offensive Andrzej Lepper the leader of Self-defence (at first – trades union, later – a political party) and in 2001 he won above 10% votes in parliamentary election. At the same time less votes won the Polish Peasants‟ Party, but their influence turned out to be durable. In 2007 Andrzej Lepper lost the parliamentary election and his party disintegrated. In last years the country area less make different from town than earlier. And in the future a territorial division will have the less importance for political market segmentation.